2005
DOI: 10.1021/jp044686j
|View full text |Cite
|
Sign up to set email alerts
|

Strong Support Effects on the Insulator to Metal Transition in Supported Pt Clusters as Observed by X-ray Absorption Spectroscopy

Abstract: The development of a new in situ probe of metallic character in supported metal clusters utilizing X-ray absorption spectroscopy is described. The technique is based on the extent of screening of the core-hole left in the neutral final state after the X-ray absorption. The technique allows for the clear differentiation between local interatomic charge transfer and more delocalized metallic screening. The particle size at the metalinsulator transition is found to depend strongly on the electron richness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 58 publications
4
27
0
Order By: Relevance
“…This model contains 44 atoms, arranged in a reasonably well-alloyed configuration, with 4 Ru͑O͒ x islands at the surface. Based on the dispersion 82 for a cluster of this size, all but 5 atoms are at the surface, and only 20% of the surface Ru atoms are oxidized. The PtRuE model is quite different, both in size and configuration.…”
Section: Discussionmentioning
confidence: 99%
“…This model contains 44 atoms, arranged in a reasonably well-alloyed configuration, with 4 Ru͑O͒ x islands at the surface. Based on the dispersion 82 for a cluster of this size, all but 5 atoms are at the surface, and only 20% of the surface Ru atoms are oxidized. The PtRuE model is quite different, both in size and configuration.…”
Section: Discussionmentioning
confidence: 99%
“…No direct catalytic data on the support influence on large Pt particles are available, but based on our study of the insulator-to-metal transition as a function of the support ionicity [21] the metal-support interaction is expected to level off for particles >2.5 nm.…”
Section: Influence Of Ionicity Of the Support On The Hydrogen Chemisomentioning
confidence: 91%
“…This oxygen electron richness is determined primarily by the ionic character of the cations in the oxide support; with electron-rich oxygens existing in basic supports with alkaline cations and electron-poor oxygens existing in acidic supports with protons or other, more covalent cations. A new analysis procedure of the Pt L 2 and L 3 near-edge structure (XANES), atomic X-ray absorption fine structure (AXAFS), and density functional theory (DFT) calculations on supported Pt clusters revealed that increasing electron richness of the support oxygen atoms affects the electronic properties of a metal particle in at least three separate ways: (i) the complete Pt density of states shifts to higher energy (lower binding energy) [7,8]; (ii) the location of the 6s, p bonding orbital (i.e., the interstitial bonding orbital [20]) moves from the metal-support interface to the surface of the Pt particles [17]; and (iii) the insulator-to-metal transition is occurring at lower particle sizes [21]. This knowledge, together with information on the dominant hydrogen adsorption sites (atop or n-fold) obtained from the Pt L 3 XANES calculations, was used to analyze previously reported neopentane hydrogenolysis kinetic data [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ramaker et al studied metal-to-insulator transition of Pt metal clusters using XAS [160]. They found that metallic screening occurred to Pt clusters as small as 12Å in diameter.…”
Section: Metalsmentioning
confidence: 99%